In vitro Elution of Penicillin, Ampicillin, Tetracycline, Tulathromycin, and Florfenicol From Plaster of Paris Beads - Merkatoris, Paul; Schleining, Jennifer; Krull, Adam; Borts, David; Fajt, Virginia (Frontiers in Veterinary Science, 2020)
The objectives of this study were to report a recipe for making antibiotic impregnated Plaster of Paris (AI-PoP) beads using penicillin, ampicillin, tetracycline, tulathromycin, and florfenicol and to determine the in vitro elution rates of those antibiotics in the beads. The AI-PoP beads were made using Plaster of Paris powder, antibiotic, and water, cured for 24 hours, sterilized by ethylene oxide, and stored up to 5 months before testing. For each antibiotic, twenty beads were combined with bovine serum in sterile tubes and incubated at 37° C on a rocker. Serum was replaced at intervals over the 14 day study period, and antibiotic concentrations were determined by high pressure liquid chromatography with mass spectrometry. Separately, in a proof-of-concept study, the growth of E. coli and T. pyogenes in eluent from 10 beads for each antibiotic was quantified by flow cytometry. Antibiotic was detected in AI-PoP bead eluent for 14 days for all but the ampicillin beads, for which antibiotic was detected for 8 days. The concentration of antibiotic in eluent was greater than the minimum inhibitory concentration (MIC) of tested bacteria for the entire study period for penicillin, tetracycline, tulathromycin, and florfenicol. The concentration of ampicillin remained greater than the MIC of E. coli for 4 days and T. pyogenes for 6 days. The colony forming units (CFU)/ml of live E. coli and T. pyogenes was reduced over a 72-hour period by 1-3 log10 CFU, with the exception of tetracycline, which reduced CFU/ml of T. pyogenes by less than log10 CFU. AI-PoP beads containing penicillin, tetracycline, tulathromycin, and florfenicol elute antibiotic well above the MIC of selected isolates for the two week study period. These antibiotics show promise for delivery in joint and wound infections.